Pengaruh Perlakuan BA dan NAA terhadap Pembentukan Akar Nenas (Ananas comosus (L). Merr.) cv. Smooth Cayenne Secara In Vitro - Rosmaina Rosmaina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
The objectives of this research are to study the effect of shoot multiplication media and subculture on root formed and survive of plantlet during acclimatization. Plant material was used that explants of pineapple (Ananas comosus (L.) Merr.) cv Smooth Cayenne which resulting from multiplication with several concentrations of BA and NAA which are subculture two times. The results of this research showed that all treatments of multiplication medium do not difference significance on explants capability to root formed and survive during acclimatization, but re-subculture effect on plantlet survival during acclimatization which all treatments at first subculture showed result better than second subcultures. It’s showed